2022
DOI: 10.1093/mnras/stac1053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspect changes on Near-Earth Asteroid phase curves

Abstract: Phase curves of asteroids are typically considered to depend solely on the scattering properties of airless particulate surfaces and the size of the object being studied. In this study, we demonstrate the additional dependence of phase curves on object shape, rotation pole orientation, and viewing geometry over an apparition. Variations in the phase curve of near-Earth asteroid (159402) 1999 AP10 over its apparition from July 2020 - January 2021 are verified to be due to aspect changes over the apparition. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Using the absolute magnitude and the radar-derived diameter D eq = 1.71 ± 0.07 km, the optical albedo is calculated as 0.25 ± 0.02, consistent with the polarimetrically-derived albedo from Belskaya et al (2009). Caution must be used when inferring physical properties from phase curve-derived parameters of NEAs, however, due to the potential for changing aspect to introduce additional brightness modulations in the phase curve that are unrelated to the scattering behaviour of the surface material (Jackson et al 2022).…”
Section: Disk-integrated Propertiessupporting
confidence: 62%
“…Using the absolute magnitude and the radar-derived diameter D eq = 1.71 ± 0.07 km, the optical albedo is calculated as 0.25 ± 0.02, consistent with the polarimetrically-derived albedo from Belskaya et al (2009). Caution must be used when inferring physical properties from phase curve-derived parameters of NEAs, however, due to the potential for changing aspect to introduce additional brightness modulations in the phase curve that are unrelated to the scattering behaviour of the surface material (Jackson et al 2022).…”
Section: Disk-integrated Propertiessupporting
confidence: 62%
“…These issues could be related to differences in the times and viewing geometries of our data relative to those used to derive the model parameters. Disentangling the effects of shape and viewing geometry on photometric phase curves can be challenging for near-Earth asteroids (e.g., Jackson et al 2022). Further work is needed to address whether discrepancies with the mutual event model (e.g., Figure 7) could be attributed to these potentially unusual photometric properties of the Didymos system.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in Jackson et al (2022), aspect effects can also influence the observed phase-curve behavior and affect the derived H and G values. To investigate any potential systematics in the Didymos phase curves, we implemented a shape-based Hapke model (Hapke 2012;Jackson et al 2022) utilizing the shape models of Didymos and Dimorphos derived from DART images taken prior to impact (Barnouin et al 2023;Daly et al 2024). In this model, the bidirectional reflectance, r BI , of each facet is calculated using…”
Section: Phase-curve Modelingmentioning
confidence: 95%
“…Finally, the Bond albedo is typically derived from the asteroid absolute magnitude H and phase parameter G in combination with the asteroid diameter (Bowell et al 1989;Fowler & Chillemi 1992). However, such quantities are susceptible to catalog biases (Pravec et al 2012) and aspect effects (Jackson et al 2022), and therefore well-constructed phase curves are required to derive an accurate value for the Bond albedo. Furthermore, phase curves can also provide additional diagnostic information on the composition of the asteroid surface (Oszkiewicz et al 2012;Penttilä et al 2016).…”
Section: Introductionmentioning
confidence: 99%